Dosimetric feasibility of using tungsten-based functional paper for flexible chest wall protectors in intraoperative electron radiotherapy for breast cancer. (14th December 2017) - Kamomae, Takeshi; Monzen, Hajime; Kawamura, Mariko; Okudaira, Kuniyasu; Nakaya, Takayoshi; Mukoyama, Takashi; Miyake, Yoshikazu; Ishihara, Yoshitomo; Itoh, Yoshiyuki; Naganawa, Shinji
Abstract: Intraoperative electron radiotherapy (IOERT), which is an accelerated partial breast irradiation method, has been used for early-stage breast cancer treatment. In IOERT, a protective disk is inserted behind the target volume to minimize the dose received by normal tissues. However, to use such a disk, the surgical incision must be larger than the field size because the disk is manufactured from stiff and unyielding materials. In this study, the applicability of newly developed tungsten-based functional paper (TFP) was assessed as an alternative to the existing protective disk. The radiation-shielding performance of the TFP was verified through experimental measurements and Monte Carlo simulations. Percentage depth dose curves and lateral dose profiles with and without TFPs were measured and simulated on a dedicated IOERT accelerator. The number of piled-up TFPs was changed from 1 to 40. In the experimental measurements, the relative doses at the exit plane of the TFPs for 9 MeV were 42.7%, 9.2%, 0.2%, and 0.1% with 10, 20, 30, and 40 TFPs, respectively, whereas those for 12 MeV were 63.6%, 27.1%, 8.6%, and 0.2% with 10, 20, 30, and 40 TFPs, respectively. Slight dose enhancements caused by backscatter radiation from the TFPs were observed at the entrance plane of the TFPs at both beam energies. The results of the Monte Carlo simulation indicated the same tendency as the experimental measurements. Based on the experimental and simulated results, the radiation-shielding performances of 30 TFPs for 9 MeV and 40 TFPs for 12 MeV were confirmed to be acceptable and close to those of the existing protective disk. The findings of this study suggest the feasibility of using TFPs as flexible chest wall protectors in IOERT for breast cancer treatment.